Isolation, Identification and Antagonism Test of Heterotrohic Bacteria in Mangrove Plants Againts Pathogenic Bacteria (Vibrio alginolyticus, Aeromonas hydrophila, and Pseudomonas sp.) - Afriza, Dinny; Effendi, Irwan; Siregar, Yusni Ikhwan (Fakultas Perikanan dan Kelautan Universitas Riau, 2019)
Heterotrophic bacteria are bacteria that are able to utilize organic matte as a source of carbon and energy. Heterotrophic bacteria live and have an important role in aquatic ecosystems. Pathogenic bacteria V. alginolyticus, A. hydrophila and Pseudomonas sp are pathogenic bacteria against fish. This study aims to isolate, identify, test the ability of the bacteria as antibacterial against pathogenic bacteria and determine the characteristics of heterotrophic bacteria using 16S rRNA sequences.this research was conducted from January to March 2019 whivh took place in the Mnagrove Area in the Marine Station Dumai, Riau Province. Based on the results of the research that has been done, it was obtained 8 pure bacterial isolates used to observe the morphology of bacterial colonies, biochemical tests and antagonism tests against pathogenic bacteria. Based on the results of the antagonism test, it was obtained the best 2 isolates for DNA analysis. The results of DNA analysis using PCR 16S rRNA method and BLAST analysis were Bacillus amyloliquefaciens strain SH20, and Bacillus cereus strain NY180